Modeling the role of banking risks on the performance of the banking system and macroeconomic variables with the DSGE model approach - Yazdan Gudarzi Farahani; Seyedhadi Arabi; Omid Ali Adeli (مدلسازی اقتصادسنجی, 2021)
The purpose of this study was to investigate the effect of banking system risks on bank performance and macroeconomic variables. For this purpose, credit, liquidity, market and operational risks were used as the most important risks of the banking system. In order to analyze the results, the dynamic stochastic general equilibrium method was used in terms of the structure of the banking system in the period 1991-2020 based on the frequency of quarterly data. In the statistical analysis section, the effect of shock from each of the mentioned risks on banking and macroeconomic variables was compared and evaluated. The results showed that most macroeconomic and banking variables showed the most reaction to market and credit risk and had the least reaction to operational and liquidity risks.